Sufistic Therapy as a Medium of Clients' Peace of Mind Treatment at Griya Sehat Syafaat 99 Semarang Clinic - Meta Malihatul Maslahat; Rika Dwi Arumaningrum; Ina Ifa Rukmana (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Abstract: In the digital era, many people are lulled by materialistic aspects and losing sight of their spiritual identity. This leads to agitation, anxiety, emptiness, and a sense of meaninglessness in one's life. As the entire problem makes the soul uneasy, people must seek alternative means of achieving peace of mind. The alternative way to achieve it is to engage in Sufistic therapy since this spiritual therapy can assist an individual in regaining peace of mind and drawing him closer to Allah.This study aims to gain a clear picture of the implementation and role of Sufistic therapy in treating clients' peace of mind. Griya Sehat Syafa'at 99 clinic in Semarang was selected as the object of the study since Sufistic therapy was applied in the clinic's healing process. This study falls under the category of field research with descriptive analytical approach.The results of this study suggest that Sufistic therapy at Griya Sehat Syafa'at 99 Semarang plays a positive role in the clients' peace of mind. It makes them feel more at ease, calm, and happy. The Sufistic therapy used here is based primarily on the therapists’ Sufistic communication with their clients. The ruqyah therapy method is used as a therapeutic medium. The Sufistic therapy used here is not primarily aimed at physical healing, but referring to self-transformation, changing the clients' thoughts and feelings in a more positive direction, gaining peace of mind, and increasing faith in Allah.